EXPLORING PEDAGOGICAL TRANSLANGUAGING IN EFL CLASSROOM: PRACTICES AND IMPLICATIONS FOR STUDENTS’ WRITING - Erlik Widiyani Styati; Riznanda Nur Annisa; Rizqi Husaini; Lulus Irawati (International Journal of English Learning and Applied Linguistics (IJELAL), 2026)
In multilingual EFL situations, pedagogical translanguaging has drawn more attention because it enhances language acquisition and writing skills. However, little study has looked at how teachers use pedagogical translanguaging in junior high school writing classes in Indonesia and how this affects students' writing. This research used a qualitative case study design and was carried out at SMPN 1 Maospati in East Java, Indonesia. Thirty-two eighth-grade students from Class 8D and one English teacher participated. Observations, semi-structured interviews, and documentation were used to gather data. The interactive model of qualitative analysis developed by Miles et al., (2014) was used to examine the data, and Poplack's (1980) typology was used to identify translanguaging techniques. To increase the validity of the results, methodological triangulation was used. The results showed that the teacher used code-switching, code-mixing, translation, and flexible usage of Indonesian and English to implement pedagogical translanguaging. Pre-, while-, and post-writing activities all involved code-switching at both the intra-sentential and inter-sentential levels. These exercises served as scaffolding techniques that helped students understand writing principles and directions. Additionally, educational translanguaging produced a low-stress, encouraging learning environment where students could use their linguistic repertoires to organize texts, come up with ideas, and convey meanings in English. In addition to reporting a positive view of translanguaging, students showed increased confidence, involvement, and proficiency in producing brief functional texts. It can be concluded that pedagogical translanguaging is an useful instructional approach for supporting EFL writing skill in multilingual classroom and should be considered in writing pedagogy, curriculum design, and teachers.